PENGUKURAN PERUBAHAN POLARISASI PADA AIR BERAS MENGGUNAKAN HAMBURAN MIE - Wahyuni Wahyuni; Ketut Sofjan Firdausi (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Have been done scattering studies of rice water using polarization method with the light sources is a green laser with a wavelength of 532 nm and variations of the density of rice water. The test samples consist of three kinds of rice water obtained from different rice tipes.Change of scattering polarization direction is perpendicular to the incident light. Then observed the changes of scattering polarization angle seen in analyzer. The result showed that the scatttering polarization angle changes produced by the green laser in the rice water is increased to the amount of rice water particles. Then changes of scattering polarization angle in qualitative influenced by the size of rice water particles.